Implementation of Consultation in Mentoring by School Supervisors in Junior High Schools - Mewoh, Angeline L.; Lengkong, Jeffry Sony Junus; Mongdong, Romi Junior (Abdurrauf Science and Society, 2025)
This study aims to describe the implementation of consultation in mentoring by school supervisors at SMP Negeri 3 Ranoyapo. This study uses a qualitative approach and case study method. The location of the study was SMP Negeri 3 Ranoyapo in South Minahasa Regency. The sources of research data were informants of school supervisors, principals, homeroom teachers and subject teachers. The data of this study were collected through interview techniques, observations, and documentation studies which were processed through analysis techniques based on the interaction model. The results of the study include: a) the implementation of consultation in mentoring by school supervisors is shown from the role of school supervisors as consultants, based on the work program of school supervisors, consideration of problems and implementing prescription and collaboration consultation procedures; b) supporting factors for the implementation of consultation in mentoring by school supervisors are the principal and school supervisor personally; and c) inhibiting factors for the implementation of consultation in mentoring by school supervisors are human resources of teachers and non-human resources